Involvement of Chromatin Remodeling Genes and the Rho GTPases RhoB and CDC42 in Ovarian Clear Cell Carcinoma - Arildsen, Nicolai Skovbjerg; Jönsson, Jenny-Maria; Bartuma, Katarina; Ebbesson, Anna; Westbom-Fremer, Sofia; Måsbäck, Anna; Malander, Susanne; Nilbert, Mef; Hedenfalk, Ingrid A. (Frontiers in Oncology, 2017)
Objective: Ovarian clear cell carcinomas (OCCCs) constitute a rare ovarian cancer subtype with distinct clinical features, but may nonetheless be difficult to distinguish morphologically from other subtypes. There is limited knowledge of genetic events driving OCCC tumorigenesis beyond ARID1A, which is reportedly mutated in 30-50% of OCCCs. We aimed to further characterize OCCCs by combined global transcriptional profiling and targeted deep sequencing of a panel of well-established cancer genes. Increased knowledge of OCCC specific genetic aberrations may help in guiding development of targeted treatments and ultimately improve patient outcome. Methods: Gene expression profiling of formalin-fixed, paraffin-embedded (FFPE) tissue from a cohort of the major ovarian cancer subtypes (cohort 1; n=67) was performed using whole-genome cDNA-mediated Annealing, Selection, extension and Ligation (WG-DASL) bead-arrays, followed by pathway, gene module score and gene ontology analyses, respectively. A second FFPE cohort of 10 primary OCCCs was analyzed by targeted DNA sequencing of a panel of 60 cancer-related genes (cohort 2). Non-synonymous and nonsense variants affecting single nucleotide variations and insertions or deletions were further analyzed. A tissue microarray of 43 OCCCs (cohort 3) was used for validation by immunohistochemistry and chromogenic in situ hybridization. Results: Gene expression analyses revealed a distinct OCCC profile compared to other histological subtypes, with e.g. ERBB2, TFAP2A and genes related to cytoskeletal actin regulation being overexpressed in OCCC. ERBB2 was however not overexpressed on the protein level and ERBB2 amplification was rare in the validation cohort. Targeted deep sequencing revealed non-synonymous variants or insertions/deletions in 11/60 cancer-related genes. Genes involved in chromatin remodeling, including ARID1A, SPOP and KMT2D were frequently mutated across OCCC tumors. Conclusions: OCCCs appear genetically heterogeneous, but harbor frequent alterations in chromatin remodeling genes. Overexpression of TFAP2A and ERBB2 was observed on the mRNA level in relation to other ovarian cancer subtypes. However, overexpression of ERBB2 was not reflected by HER2 amplification or protein overexpression in the OCCC validation cohort. In addition, Rho GTPase dependent actin organization may also play a role in OCCC pathogenesis, and warrants further investigation. The distinct biological features of OCCC discovered here may provide a basis for novel targeted treatment strategies.